(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Marine chlorophyll plays aprimary role in conserving the marine ecosystems which are essential for the marine food web. Understanding the variation of Chl-a (or Phytoplankton) over the aquatic systems is necessary for various applications like predicting the potential fishing zone. Advancement in the remote sensing with multispectral sensors, image processing techniques and tested remote sensing models together provide a powerful tool to analyse and monitor the ocean parameters. Ocean colour remote sensing is a simple and easiest tool which is used for the quantifying the chlorophyll. In this study, we analyse the spatial and temporal variation of chlorophyll pattern in the marine surface for the Gulf of Manner of Indian coastal waters. The Chl-a concentrations were estimated from the standard chlorophyll algorithm. Moderate resolution imaging spectroradiometer (MODIS) satellite data were effectively used to quantify the spatial and temporal changes of surface chlorophyll. The outcome of this analysis contributes to deliver an advance tool to analyse the long-term changes in phytoplankton pigment concentration in coastal and open ocean.